Rare Earths in the Trade Dispute Between the US and China: A Déjà Vu - Marc Schmid (Intereconomics, 2019)
The trade dispute between the US and China has reached a point where export restrictions on rare earths have become a possible means for sanction. This contribution provides a succinct analysis of the current dependency of the US on rare earths from China and draws parallels to the events during the rare earth crisis of 2010 and 2011, which was caused by geopolitical tensions between Japan and China. Respective risks associated with restrictions on the trade of rare earths are considered. Findings suggest that Europe could be affected as well and should be better prepared to mitigate supply disruptions in rare earth trade. Potential mitigation strategies and consequences of the current developments for Europe are also discussed.
Keywords: 330